Cloud Storage Promotion Strategy Through Pt Telkom Regional VII Instagram - Mathory, Eljihad Akbari Syukriah; Saharuddin, Aulia (Al-Makki Publisher, 2023)
Based on the results of the pre-research that has been conducted, PT Telkom Regional VII is not actively promoting Cloud Storage products digitally, only maximizing the sales force at Telkom Plaza. Therefore, this study aims to make a promotional video that is uploaded on PT Telkom Regional VII's Instagram using the AIDA method as a Cloud Storage product promotion strategy. The research method used in this study is Descriptive Qualitative. This qualitative descriptive approach uses data collection through structured interviews, questionnaire distribution, observation, and documentation of several related parties that can assist researchers in the research process. The results of this study show that the four AIDA elements used, namely Attention, Interest, Desire, and Action can be variables in measuring Cloud Storage promotion at PT Telkom Regional VII because the four variables have a positive impact in this regard through promotional videos.